E-Government Model Design for Volcano Eruption Disaster Risk Reduction in Agam Regency, West Sumatra - Sucia Angelia Tika; Rukuh Setiadi (Pusbindiklatren Bappenas, 2026)
The eruption of Mount Marapi in Agam Regency poses a high risk to public safety and requires a responsive and sustainable disaster management system. However, information dissemination and inter-agency coordination remain limited and have not optimally utilized the potential of digital technology in Disaster Risk Reduction (DRR), particularly for volcanic hazards that are complex and difficult to predict. This study aims to develop an e-government framework for diagnosing volcanic eruption disaster risk reduction and to design an e-government model based on smart governance principles. A multiple-method approach was employed, including a review of existing policies and regulations, a survey of community perceptions, and an assessment of institutional and infrastructure readiness. The findings indicate that the community supports the use of digital technology in disaster management; however, the effectiveness of information systems, training programs, and Information and Communication Technology (ICT) infrastructure remains low. The proposed e-government model consists of six main strategies: (1) regulatory strengthening, (2) digital-based public outreach, (3) stakeholder engagement, (4) technology capacity building, (5) development of integrated information systems, and (6) efficiency in fund management. This model is expected to enhance community preparedness, accelerate emergency response, and improve the efficiency and transparency of volcanic disaster risk governance in Agam Regency.